HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA-KAKI DENGAN HASIL SHOOTING KE ARAH GAWANG PADA TIM SEPAKBOLA SMAN 1 BENGKALIS - Nawab, Muhammad; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Problems in this study originated from the observation that the author found in the field, it has not targeted the results of shooting on goal in the Football team SMAN 1 Bengkalis. The purpose of this study was to determine the relationship leg muscle strength and coordination of the ankle with the results of shooting on goal in the Football team SMAN 1 Bengkalis. The population in this study is a Football team SMAN 1 Bengkalis, amounting to 18 people using the total engineering side where all the population sampled, to obtain research data used Leg Dynamometer tests, foot-eye coordination by catching throwing the ball to the wall with the foot and the shooting into the goal. Data were analyzed by simple and multiple product moment Based on the analysis of the data found that the results obtained from leg muscle strength have a relationship with the results of shooting on goal in the Football team SMAN 1 Bengkalis. leg muscle strength have a relationship with the results of shooting on goal in the Football team SMAN 1 Bengkalis with rhitung (0.480)> rtab (0.468), the results obtained from the foot eye coordination have a relationship with the results of shooting on goal in the Football team SMAN 1 Bengkalis with means , rhitung (0,548)> rtab (0.468). There is a relationship jointly between leg muscle strength and coordination ankle against the shooting on goal in the Football team SMAN 1 Bengkalis with rhitung (0.618)> rtab (0.468).Keywords : leg muscle power, eye-foot coordination, shooting, football